Reconstruction of Axillary Defect due to Necrotizing Fasciitis and Debridement Using a Free-Flap Transfer: A Report of Three Cases - Ogawa, Haruo; Nakayama, Haruki; Nakayama, Shinichi; Tahara, Shinya (Journal of Reconstructive Microsurgery Open, 2021)
Background Necrotizing fasciitis is a well-known disease that causes extensive tissue infection and requires radical debridement of the infected tissue. It can occur in all parts of the body, but there are few reports of necrotizing fasciitis in the axilla. We treated three patients with axillary necrotizing fasciitis.Methods In all cases, patients were referred to us after radical debridement of the infected soft tissue in the emergency department. At the first visit to our department, there were fist-sized soft tissue defects in the axilla. Moreover, the ipsilateral pectoralis major and latissimus dorsi muscles were partially resected because of the debridement of necrotizing fasciitis. In all cases, the ipsilateral thoracodorsal vessels were severely damaged and free-flap transfer was performed to close the axillary wound.Results All free flaps survived without complications. The patient's range of motion for shoulder abduction on the affected side was maintained postoperatively.Conclusion If necrotizing fasciitis occurs in the axilla, tissue infection can spread beyond it. In such a case, free-flap transfer can be an optimal treatment. Radical resection of the infected tissue results in the absence of recipient vessels in the axilla. Surgeons should bear in mind that, because of radical resection of the infected tissue, they may need to seek recipient vessels for free-flap transfer far from the axilla.
Keywords: axilla; necrotizing fasciitis; free flaps